Synchrony of the first division as an index of the blastocyst formation rate during embryonic development - Mizobe, Yamato (Reprod Med Biol, 2017)
PURPOSE: To devise an uninvasive selection system for human embryos with high developmental potential after a single oocyte retrieval cycle by comparing the in vitro and in vivo effectiveness of first division synchrony against subsequent embryonic developmental stages. METHODS: The effects of using assisted reproductive technology on 948 embryos that were produced in 137 cycles were examined by dividing the embryos into “early cleavage” (first division within 25.90 hours) and “late cleavage” (first division at or after 25.90 hours) groups and comparing the blastocysts and good‐quality blastocyst formation rates between the two groups. These two groups were each divided further into “high synchrony” (first division synchrony within 3.96 hours) and “low synchrony” (first division synchrony at or after 3.96 hours) groups. The blastocysts, good‐quality blastocyst formation rates, and pregnancy rates were compared among these four groups. RESULTS: Both the blastocysts and good‐quality blastocyst formation rates were significantly higher in the early‐cleavage groups than in the late‐cleavage groups. The blastocyst formation rate of the latter was also significantly increased in the high‐synchrony, compared with the low‐synchrony, group. CONCLUSION: First division synchrony in a single oocyte retrieval cycle could be a useful assessment of the blastocyst formation rate that enables the selection of viable embryos at an early stage of culture.